2017
DOI: 10.5897/jvmah2016.0527
|View full text |Cite
|
Sign up to set email alerts
|

Clinical survey on major ruminant diseases in Kola Tembein and Tanqua Abergelle Districts, Central Zone of Tigray, Northern Ethiopia

Abstract: Diseases are the major detriment in ruminant production and productivity in the study districts. A cross sectional study was conducted to assess the major animal health constraints of ruminants. 461 species of sick ruminants were examined and diagnosed tentatively. Similarly, samples were collected and identified in the laboratory for confirmation of the cases. Of the clinically identified ruminant diseases, sheep and goat pox (11.93%), abortion (8.24%), pasteurellosis (8.46%), lice infestation (9.98%), tick i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
3
3
Order By: Relevance
“…[ 10 ] Have found a prevalence of 21.9% which is below to our study. In the current study the prevalence is higher as compared to previous report (8.46%) by [ 6 ] in the same study districts. This high prevalence in our study may be due to high environmental stress factors (heat, drought, feed and water shortages) in the study districts since 2015.…”
Section: Main Textcontrasting
confidence: 80%
See 1 more Smart Citation
“…[ 10 ] Have found a prevalence of 21.9% which is below to our study. In the current study the prevalence is higher as compared to previous report (8.46%) by [ 6 ] in the same study districts. This high prevalence in our study may be due to high environmental stress factors (heat, drought, feed and water shortages) in the study districts since 2015.…”
Section: Main Textcontrasting
confidence: 80%
“…A 5% absolute precision and 95% confidence interval was used to determine the sample size. An expected prevalence of 8.46% was taken to determine the maximum sample size [ 6 ]. Accordingly, 119 animals were used for the present study.…”
Section: Main Textmentioning
confidence: 99%
“…On the other hand, the prevalence of mite infestation in the current study was lower than the findings of Guash et al, 24 Fesseha et al, 25 Ambilo and Melaku 26 ; Agumas et al, 12 and Asmare et al 5 who reported an overall prevalence of 11.57%, 34.6%, 34.56%, 40%, and 41.76% in different parts of Ethiopia, respectively. The variation in the prevalence of mange mite infestation in different areas of the country might be related to changes in agro-climate conditions as well as management systems.…”
Section: Discussioncontrasting
confidence: 79%
“…The prevalence of mite infestation was relatively higher than that reported by Mandado et al, 21 who reported a prevalence of 4.67% and species-level prevalence of 2.67% Sarcoptes, 1.33% Demodex, and 0.67% mixed (Sarcoptes and Demodex); Pal et al, 22 who reported a prevalence of 4.68% and species-level prevalence of 2.08% Sarcoptes, 1.83% Demodex, and 0.78% mixed (Sarcoptes and Demodex); Dansure and Belay, 23 who reported a prevalence of 3.11% and species-level prevalence of 1.92% for Sarcoptes, 1.02% for Demodex, and 0.11% mixed infestation; and Sheferaw et al, 2 who reported a prevalence of 3.98% and species-level prevalence of 2.61% Sarcoptes 1.23% Demodex and 0.14% mixed infestation. On the other hand, the prevalence of mite infestation in the current study was lower than the findings of Guash et al, 24 Fesseha et al, 25 Ambilo and Melaku 26 ; Agumas et al, 12 and Asmare et al 5 who reported an overall prevalence of 11.57%, 34.6%, 34.56%, 40%, and 41.76% in different parts of Ethiopia, respectively. The variation in the prevalence of mange mite infestation in different areas of the country might be related to changes in agro-climate conditions as well as management systems.…”
Section: Discussioncontrasting
confidence: 79%
“…One of the major constraints to goat production in Tanqua Aberegelle district is high occurrence of abortion cases [ 5 ]. Farmers and experts have consistently reported a significant number of abortions annually, raising concerns about the underlying factors contributing to this issue.…”
Section: Introductionmentioning
confidence: 99%